Outdoor artificial light at night and risk of non-Hodgkin lymphoma among women in the California Teachers Study cohort. (December 2020) - Zhong, Charlie; Franklin, Meredith; Wiemels, Joseph; McKean-Cowdin, Roberta; Chung, Nadia T.; Benbow, Jennifer; Wang, Sophia S.; Lacey, James V.; Longcore, Travis
Highlights: The New World Atlas of Artificial Night Sky Brightness was used to assess exposure to light at night. There was increased risk of NHL for those in highest quintile of light at night. The risk association was strongest for the DLBCL subtype. The World Atlas is a unique resource for studying health effects associated with light at night. Abstract: Background: Outdoor artificial light at night (ALAN) has been implicated in a growing number of adverse health outcomes. ALAN is believed to disrupt circadian rhythms and has been associated with increased inflammation, one of the hallmarks of cancer. We examined the association between outdoor ALAN and a cancer strongly associated with autoimmune and inflammatory conditions, non-Hodgkin lymphoma (NHL), in the prospective California Teachers Study cohort. Methods: Outdoor ALAN was assigned to participant addresses at study baseline (1995−96) through use of the New World Atlas of Artificial Night Sky Brightness. Among 105, 937 women followed from 1995 to 2015, linkage to the California Cancer Registry identified 873 incident cases of NHL. Age-stratified Cox proportional hazards models were used to calculate hazard ratios (HR) and 95 % confidence intervals (95 %CI) for overall NHL and the most common NHL subtypes; diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL) and chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). Multivariate analyses adjusted for previously reported subtype specific covariates (e.g. body mass index (BMI) for DLBCL). Results: Compared to the lowest quintile, participants residing in the highest quintile of outdoor ALAN at baseline were more likely to develop NHL (HR = 1.32, 95 %CI = 1.07−1.63), and, in particular, DLBCL (HR = 1.87, 95 %CI = 1.16−3.02). The elevated risk for DLBCL remained statistically significant after adjusting for age, race/ethnicity, BMI, and socioeconomic status (DLBCL:HR = 1.87, 95 %CI = 1.16−3.02, NHL:HR = 1.32, 95 %CI = 1.07−1.63). There was no association between ALAN and FL or CLL/SLL. Conclusion: DLBCL risk was elevated among women residing in neighborhoods with greater outdoor ALAN. Future research in circadian disruption and DLBCL may clarify potential biological processes implicated in this association.